Mobile eLearning Application with Chatbot and AI as Student Academic Mentor - Callupe-Zuñiga, Elvis; Cabanillas-Carbonell, Michael (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The gap in education is centered on access to inter-active and accessible educational tools for all, however, it is changing thanks to globalization and technological advancement with new tools that promote continuous learning. A prototype of a mobile application with an artificial intelligence (AI) chatbot for academic mentoring has been developed. For this purpose, the ADDIE methodology was used, as it provides a structured and flexible framework that allows the development to be adjusted to the changing needs of the project. The prototype facilitates access to academic resources, resolves concerns immediately and offers personalized support to optimize the educational experience. The quality of the prototype was evaluated by experts and users, who appreciated its technology, relevance, integration, usefulness, satisfaction and mentoring, obtaining an average score of 4.47 and 4.48 respectively, which reflects a high level according to the criteria established to improve the educational experience.